UKRAINIAN CULTURE of the end of the ХІХ – beginning of the XX cc. as A FACTOR OF FORMATION OF NATIONAL MENTALITY - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to influence of main trends, styles of Ukrainian culture of the end of the ХІХ – beginning of the XX cc. on the process of formation of Ukrainian people national consciousness. Special attention is given to literature and painting.